KEEFEKTIFAN LKPD (LEMBAR KERJA PESERTA DIDIK) TERHADAP PRESTASI HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM PANCAINDRA MANUSIA KELAS IV SDN MRICAN 2 - Nur Malasari, Rosa; Sahari, Sutrisno; Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of Student Worksheets (LKPD) at SDN Mrican 2 is still considered less interactive and has not optimally utilized digital media. This study aims to determine the effectiveness of using Student Worksheets (LKPD) on student achievement in the topic of the human sensory system for fourth-grade students at SDN Mrican 2. This research used the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 27 fourth-grade students at SDN Mrican 2. Data collection techniques included observation, interviews, and evaluation tests. Data analysis techniques involved quantitative data analysis and qualitative descriptive analysis. The results of this study indicate that the effectiveness test through evaluation questions was conducted in two stages: limited trial and large-scale trial. The students’ mastery learning percentages were 80% and 88.2%, respectively, with scores above the minimum mastery criteria (KKM) of 75. Based on these results, it can be concluded that Wordwall-based LKPD is highly effective in improving students’ learning outcomes.